Comparative Analysis of Teacher Qualifications and Resources in Bamyan's Public and Private Schools - Zahra Kazemi (e-Bangi Journal of social science and humanities, 2026)
Educational equity in conflict-affected settings depends heavily on whether schools can staff qualified teachers and provide basic learning resources. This study examines how teacher qualifications and resource availability differ between public and private primary schools in Bamyan Province, Afghanistan, and considers the implications of these disparities for equity. Using a qualitative comparative design, the study drew on semi‑structured interviews with 60 teachers across public and private schools, supported by non‑participant school observations and review of available school documents (e.g., staffing records and inventories where accessible). Data were analysed through thematic coding and cross‑case comparison to identify patterns associated with school type. Findings indicate that private schools tend to attract teachers with higher formal qualifications and more frequent exposure to professional development, alongside better access to teaching and learning materials and more stable infrastructure. Public schools were characterised by larger classes, limited instructional materials, constrained facilities, and fewer opportunities for teacher development—conditions that teachers associated with reduced instructional quality and uneven learner opportunities. The study argues that closing equity gaps in Bamyan requires targeted investment in public schools, transparent minimum standards for staffing and resources, and practical support for teacher development in hard‑to‑reach areas. These findings contribute context‑specific evidence to ongoing debates on how public–private disparities shape educational equity in fragile contexts.